AUGMENTED REALITY OF HEART IN TEACHING GROSS ANATOMY OF THE HEART: A LESSON LEARNED - Hikmawati Nurrokhmanti,; Dyah Samti Mayasari; Nisrina Nabila; Annisa Maulidina; Putrika Gharini (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2022)
Background: Anatomy is a crucial science for medical students, the deep understanding on material would help students dealing with clinical context such give a better explanation to patients until having better performance in doing clinical procedure and dissecting ability as a surgeon. Nevertheless, having a deep understanding and memorizing anatomy would need abundant effort. Several strategies combined with fit learning media will give great advantages for the students. This study is aimed to explore innovation in teaching anatomy by using augmented reality (AR) within a case-based discussion.Methods: A qualitative approach was used, in depth interview with teachers who facilitate the discussion and focus group discussion with the students. A thematic analysis was done in analyzing the data.Results: Overall, the teachers and student were satisfied with the innovation. Several themes were identified from students’ point of view such visualization, content, technical problem, and the need of teachers. The most important success factor of AR usage was its visualization i.e., orientation, and visual spatial ability.Conclusion: Combination case-based discussion with AR give promising strategies in understanding anatomy of heart. Using AR should consider several limitations of AR regarding to its visualization. Also considering the perceived advantages from the students, the usage of AR will be limited as supplement, a supporting media for having deep understanding on anatomy.